SAT-217 Paraganglioma in Two Unrelated Kinyarwanda-Speaking Patients in Anatomically Distinct Sites - Ejaz, Sadia (J Endocr Soc, 2020)
Introduction: Capable of generating excess catecholamines, untreated extra-adrenal paragangliomas (PGL) result in severe cardiovascular morbidity and mortality. Increasingly, a hereditary basis can be identified to underlie PGLs, though such data is largely absent in non-Caucasian populations. Case 1: A 43 yr. old Kinyarwanda-speaking woman from DR Congo presented with left lower extremity edema and hypertension, with blood pressure of 154/86 while on spironolactone, HCTZ and furosemide. Ultrasound was negative for a DVT; abdominal CT revealed a 3 cm necrotic mass, inferior to the duodenum and abutting the IVC and aorta, as well as 2 bladder wall lesions. EUS-guided FNA revealed a keratin-negative neuroendocrine tumor. Urinary 24hr norepinephrine (NE) was high at 185 mcg [15–80]. Urinary 24hr normetanephrine (NM) was high at 1404 mcg [119-451; hypertensive <900]. MIBG scan confirmed avidity in the aortocaval mass. Despite lack of bladder uptake on MIBG, pathology similarly pointed to PGL. Surgery included excision of bladder, pelvic nodes, uterus, and aortocaval tumor. Post-op, urinary 24hr NE was 18 mcg and NM was 297 mcg, both normal. One year later, MIBG/SPECT and CT of the abdomen were negative for recurrence. A GeneDx panel of 12 PGL/PCC mutations was negative. Case 2: An unrelated 41 yr. old Kinyarwanda-speaking woman from Rwanda, with prior history of preeclampsia and multiple miscarriages, presented with palpitations, headaches and hypertension. Echo showed a 4 cm mass posterior to the left atrium; the mass was(18)F-FDG PET-avid. Video-assisted thoracoscopy was performed yet the tumor’s vascularity precluded a biopsy. Biopsy of mediastinal mass after performing thoracotomy was consistent with PGL. Plasma NM was high at 7.1 nmol/l (<0.90), consistent with PGL and she underwent complete removal of the tumor. Testing for SDHB mutation was negative. Symptoms resolved and antihypertensives were discontinued. Follow-up plasma NM was 0.55 nmol/l 1-year post op and remained normal for six years of follow-up. Discussion: Less than 10% of PGLs are known to involve the mediastinum or bladder (1). In familial PGL, the most commonly identified non-syndromic mutations involve SDHD, SDHAF2, SDHB, SDHD, SDHC, VHL, and MAX. Tumorigenesis in a sizable fraction of PGLs is not well understood. Conclusion: We present two cases of extra-adrenal PGL, both exhibiting similar age, sex and geographic ancestry. Our cases raise questions that require active investigation regarding additional environmental and/ or genetic factors which might predispose to PGLs in uncommon anatomic sites. References: (1) Erickson D et al. J Clin Endocrinol Metab, 2001 (2) Martins et al. Int J of Endocrinol, 2014